(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the concordance between indication of cold knife conization by cervical cytology (CC), biopsy, or large loop excision of the transformation zone (LLETZ), and the anatomopathological report of surgical specimens of patients with precancerous lesions of the cervix or cervical cancer. In addition, to observe the presence of residual lesion after LLETZ in cases of microinvasive squamous cell carcinoma (SCC) and margins with high-grade squamous intraepithelial lesion (HSIL). To this end, a retrospective study was conducted involving 82 women with cervical intraepithelial lesions or cancer aged between 28 and 71 years. Women had either CC, biopsy, or LLETZ between January 2014 and January 2020 and had cold knife conization indicated according to procedure results. Surgical indication was the result of CC in 30.5% of patients; in 12.2%, it was due to cervical biopsy, and in 24.4% of cases, it was due to CC confirmed by biopsy. Moreover, 32.9% of patients had the surgery done because of compromised margins after LLETZ procedure. Agreement was found in 57.3% of surgical indications, and 42.7% did not show concordance. Residual lesion was observed in 55.6% of women who underwent LLETZ, but in the group of microinvasive squamous cell carcinoma (SCC), there was a rate of 60% of no residual lesion. Therefore, it indicates that LLETZ appears to be an effective treatment for microinvasive SCC of the cervix, and a complementary surgery with cold knife conization seems not to be required when there are compromised margins with HSIL.